Efectos de la corrupción mexicana en el emprendimiento de EE.UU. - Adrianzen Vizcarra, Alvaro Alejandro (2023)
This paper studies the effects of Mexican and American corruption on the level of entrepreneurship in the United States and other macroeconomic variables using quarterly data from 2006q2 to 2020q1. The empirical analysis is performed by means of a Bayesian vector autoregressive (BVAR) model, which allows us to incorporate prior information about the study phenomenon and, at the same time, outperforms frequentist VAR models in the case of small samples. The results show that Mexican corruption has a negative effect on the level of entrepreneurship in the United States, which is evidence in favor of the sand the wheels hypothesis and the contagion effect of corruption. This effect is significant since the initial periods and takes a long time to disappear. This can be explained by the fact that the increase in Mexican immigration product of the contagion effect of corruption has a negative effect on local US entrepreneurs, negatively affecting the level of total entrepreneurship in the country. On the other hand, it is found that the Mexican and American corruption shocks have a negative but less permanent effect on the economic growth of United States, which again reinforces the hypothesis that corruption ends up generating administrative burdens that hinder the growth and productivity of a country.